Machine vs. human, who makes a better judgment on innovation? Take GPT-4 for example - Du, Mark (Frontiers in Artificial Intelligence, 2023)
Introduction Human decision-making is a complex process that is often influenced by various external and internal factors. One such factor is noise, random, and irrelevant influences that can skew outcomes. Methods This essay uses the CAT test and computer simulations to measure creativity. Results Evidence indicates that humans are intrinsically prone to noise, leading to inconsistent and, at times, inaccurate decisions. In contrast, simple rules demonstrate a higher level of accuracy and consistency, while artificial intelligence demonstrates an even higher capability to process vast data and employ logical algorithms. Discussion The potential of AI, particularly its intuitive capabilities, might be surpassing human intuition in specific decision-making scenarios. This raises crucial questions about the future roles of humans and machines in decision-making spheres, especially in domains where precision is paramount.